New currents in the research on esotericism and mysticism - Maarit Leskelä-Kärki; Tiina Mahlamäki (Donner Institute, 2022)
The current 29th volume of Scripta Instituti Donneriani Aboensis is based on a symposium arranged by the Donner Institute and the research project ‘Seekers of the New: Esotericism and the Transformation of Religiosity in the Modernising Finland’ at the University of Turku in June 2017, under the title: ‘Approaching Esotericism and Mysticism: Cultural Influences’. All the articles published in this volume were initially presented as papers at this conference and have, through a double-blind peer-review process, been selected for this volume.